Pembinaan Konsep Psiko-Hisbat Untuk Pengurusan Insan Berteraskan Islam - Poad, Afifi Farhana Mhd (2023)
Islamic-based human management is a method of human management based on Islamic teachings that includes internal and external aspects. Among the main aspects that has been focussed in the human management based on Islam is the aspect of surveillance which consists of the spiritual surveillance, intellect, heart and desires of a human being. These four aspects are specific components of psychology which is an important aspect to be monitored to produce a good well-being in terms of emotional, spiritual and physical. However, until now, problems related to human psychology are seen to be increasingly worried to some extent that there are some issues involving extreme stress or depression that lead to suicide and so on. The question arised, is there an existing concept of Islamic psychological surveillance? how can a psychological surveillance approach in Islamic -based human management be done? and how can Islamic concept of hisbat can be integrated as a concept of human psychological surveillance? Based on these questions, this study aims to achieve three objectives. First, to identify the basic concepts of Islamic psychology and accountability in Islamic -based human management. Second, to analyze the concept of Islamic psychology and hisbat to build the concept of psycho-hisbat for Islamic-based human management. Third, to formulate the concept of psycho-mathematics for human management based on Islam. To achieve all these objectives, this study uses a basic qualitative research design through an inductive approach conducted in two phases.